Anti-inflammatory Effect of n-Hexane Fraction of Kentut leaves (Paederia scandens L.) on Male White Rats (Rattus novergicus) - Yazid, Muhammad Ilfan; Rijai, Laode; Ahmad, Islamudin (Journal of Pharmaceuticals and Natural Sciences, 2024)
The anti-inflammatory effect of fart plant leaf extract (Paederia scandens L.) on white rats (Rattus norvegicus) has been carried out. This research shows that the effective dose of the n-hexane fraction of P. scandens leaf extract provides the best anti-inflammatory effect on white rats' feet soles. The study used an artificial edema formation method and periodically measured the volume of white mice's legs using a plethysmometer. The doses used for the extract are 100mg/200g BW, 150mg/200g BW, and 200mg/200g BW. The research data was observed visually. The effective dose of P. scandens leaf extract, which has the best anti-inflammatory effect, is 150mg/200g BW.